Late Quaternary evolution of the La Cantera Fault System (Central Precordillera, Argentina): A morphotectonic and paleoseismic analysis - Perucca, Laura Patricia A. (2015)
The La Cantera Fault System (LCFS) is the most active Quaternary structure in the Central Precordillera of SanJuan, in central-western Argentina; the system extends for 47 km along the intermountain valley that separatesthe Sierra de La Cantera and La Invernada, north of the San Juan River. The average fault trend is 20°; it dips atangles varying between 15° and 30° W in the northern section, to approximately 40° W in the central section,and up to 60° W in the southern section. The fault affects Holocene to recent alluvium deposits in the westernpiedmont of the Sierra de La Cantera and is defined by a series of landforms found in compressive tectonicenvironments, including simple and compound counterslope fault scarps, staircased alluvial terraces, sagponds, flexural scarps, aligned springs, broom-shaped drainage patterns, river diversions, beheaded channels,changes in incision depths, sinuosity and a river gradient along channels. Trench investigations indicated thatat least three events occurred in the past 1.1?10.1 ky. The topographic profiles of the selected channels andinterfluves cutting across the northern and central trace of the fault were analyzed using a Stonex Vector GPS differentialsystem to establish the relationship between the topography and slope of the rivers. This morphometricanalysis of scarps indicates that active tectonics have played an essential role in controlling the drainage patternin the piedmont, leading the rivers to adjust to these slope variations. Based on the analyzed geomorphologic,stratigraphic and structural characteristics, the LCFS is considered to be a relevant seismogenic source in the intraplateportion of southern South America, with a recurrence interval of at least 2000 ± 500 years for moderatemagnitude earthquakes during the last 11,000 years.